Relationship between serum expressions of miR-129 and miR-205 and vascular calcification in patients with chronic kidney disease without dialysis - He Lei; Li Ya-jing; Lu Rui; Bai Ya-Ling; Jin Jing-Jing; Cheng Mei-Juan; Zhang Sheng-Lei; Xu Jin-Shen (Linchuang shenzangbing zazhi)
ObjectiveTo explore the relationship between serum levels of miR-129 and miR-205 and vascular calcification in non-dialysis patients with chronic kidney disease （CKD）.MethodsFrom June 2020 to January 2021，54 CKD inpatients were selected as research subjects. According to the scores of coronary artery calcification，they were divided into two groups of non-calcification （n=21） and calcification （n=33）. The serum levels of miR-129，miR-205 and Runx2 of two groups were detected by quantitative polymerase chain reaction （PCR）.The relevant clinical data between two groups were compared. Spearman’s correlation analysis was performed for evaluating the correlations between miR-129，miR-205，Runx2 and vascular calcification. Logistic regression analysis was employed for analyzing the risk factors of vascular calcification. And receiver operating characteristic （ROC） curve was plotted for examining the diagnostic values of miR-129，miR-205 and Runx2 alone and in combinations in diagnosing vascular calcification in CKD patients.ResultsThe online tool TargetScan （http：//www.targetscan.org） was used for targeting and predicting Runx2-related miRNAs. The results hinted at potential binding sites of miR-129，miR-205 and Runx2.Serum levels of miR-129 and miR-205 were lower in calcification group than those in non-calcification group. And Runx2 level was higher than that in non-calcification group （P<0.05）.Spearman’s correlation analysis indicated that the expressions of miR-129 （r=-0.445，P<0.05） and miR-205 （r=-0.560，P<0.05） were negatively correlated with vascular calcification while expression of Runx2 positively correlated with vascular calcification （r=0.28，P<0.05）.Logistic regression analysis showed that advanced age，high phosphorus and low levels of miR-129 and miR-205 were independent risk factors for vascular calcification. ROC curve analysis showed that the area under the ROC curve （AUC） of miR-129，miR-205 and Runx2 for diagnosing vascular calcification were 0.763，0.831 and 0.666 respectively. AUC of pairwise combination was miR129+205=0.856，miR-129+Runx2=0.798 and miR-205+Runx2=0.823；AUC of triple combination 0.851.ConclusionThe serum expressions of miR-129 and miR-205 are correlated with the extent of vascular calcification in non-dialysis CKD patients. Low miR-129/miR-205 is an independent risk factor for vascular calcification. Both factors are expected to become potential biomarkers for vascular calcification in non-dialysis CKD patients.